Maternal Mortality Ratios in 2852 Chinese Counties, 1996-2015, and Achievement of Millennium Development Goal 5 in China: A Subnational Analysis of the Global Burden of Disease Study in 2016. Issue 3 (September 2019) - Liang, J.; Li, X.; Kang, C.; Wang, Y.; Kulikoff, X.R.; Coates, M.M.; Ng, M.; Luo, S.; Mu, Y.; Wang, X.; Zhou, R.; Liu, X.; et al.
Abstract : ( Lancet . 2019;393:241–252) Mortality for both mother and child have been falling at impressive rates in China over the past 2 decades. Nationwide, maternal mortality dropped from 111.0 per 100, 000 livebirths in 1990 to 21.8 per 100, 000 livebirths in 2015. However, child mortality has varied substantially among counties and maternal mortality might also vary widely among counties. Identifying counties experiencing less progress could help guide the Chinese government in allocating extra resources as needed to meet the Millennium Development Goal 5 (MDG 5) of decreasing the maternal mortality rate by 75% between 1990 and 2015. This study aimed to estimate the maternal mortality ratio in 2852 counties in China between 1996 and 2015 and determine the effects of key factors such as economic development and maternal education on maternal mortality.